Інвестиційний розвиток підприємств харчової промисловості: сутність та підходи до оцінювання - Михайлик, Ольга Михайлівна; Демиденко, Олексій Юрійович (My University, 2024)
У статті визначено сутність поняття «інвестиційні ресурси» у сучасних вітчизняних наукових дослідженнях та аргументовано, що до інвестиційних ресурсів підприємств харчової промисловості варто віднести: власні кошти підприємства, позикові кошти (кредити, облігації), прямі іноземні інвестиції та державні гранти та субсидії. Обґрунтовано, що інвестиційні ресурси є багатокомпонентною категорією, яка забезпечує стратегічний розвиток підприємств та сприяє підвищенню їхньої стійкості й ефективності на ринку. Визначено, що технічне переоснащення та модернізація виробництва представляють собою пріоритетний напрям впровадження новітнього обладнання, а автоматизація та роботизація виробничих процесів дозволяють знизити витрати на виробництво, підвищити продуктивність праці та забезпечити стабільну якість продукції. Розглянуто основні напрямки впровадження інновацій та цифрових технологій. Запропоновано оцінювання інвестиційного розвитку підприємств харчової промисловості. The article defines the essence of the concept of "investment resources" in modern domestic scientific research and argues that the investment resources of food industry enterprises should include: the company's own funds, loan funds (loans, bonds), foreign direct investments, and state grants and subsidies. Enterprises should include: the company's own funds, loan funds (loans, bonds), foreign direct investments, and state grants and subsidies. It is substantiated that investment resources are a multi-component category that ensures the strategic development of enterprises and contributes to increasing their stability and efficiency on the market. It was determined that technical re-equipment and modernization of production are a priority direction for the introduction of the latest equipment, and automation and robotization of production processes allow to reduce production costs, increase labor productivity and ensure stable product quality. Among the main areas of innovation and digital technology implementation in the context of investment development of food industry enterprises, the following should be considered: automation of production processes, Internet of Things (IoT) in production, quality control systems, digital duplicates, blockchain technologies, energy-saving technology, development of environmentally friendly production, expansion of the product range, assurance of product quality and safety, marketing strategies and brand development, expansion of logistics capacities, improvement of energy efficiency, investment in human resources. The introduction of measures in these directions will contribute to increasing the efficiency of operations, improving the quality of products, increasing the volume of production and ensuring sustainable development in the conditions of the modern competitive market. An assessment of the investment development of food industry enterprises is proposed based on a comprehensive approach, which includes the analysis of financial indicators, technological innovations, market factors and economic prospects.
Keywords: інвестиційний розвиток; інвестиційні процеси; investment development; evaluation; кафедра економіки і права